Penggunaan Model DeLone Dan McLean Dalam Mengukur Kesuksesan Aplikasi Go-Jek Di Palembang - Erwin erwin; Andri Wijaya (Universitas Katolik Musi Charitas, 2019)
Go-jek application is an online transportation application by the children of the nation which has caused many phenomena since it was first launched. Based on